Compare the Results Between Model Laboratory-test for Rigid Pavement and EverStressFE Software Analysis. (2017) - Daniel, Christian Gerald; Chairuddin, Firdaus
Abstract: EverStressFE is a 3D finite element modeling software that can be used to analyze the multilayer model pavement (up to four layers possible), which requires elastic modulus and Poisson's ratio of each layer as an input value. The purpose of this paper is to develop a comparison between EversStress-FE-based analysis and laboratory test results and determine the accuracy of the software. In this study, displacement and microstrain behaviors are compared. The vertical strain governing at both the top and bottom fiber of the concrete layer from the laboratory test are 38 and 44, respectively, compared to the EverStressFE result (gz <5.65) (in microstrain). Displacement at the center is 3.4 mm and 0.3 mm according to laboratory test and EverStressFE, respectively. The outcome shows that results of EverStressFE are approximately 10 times smaller than the laboratory test result in terms of displacement and microstrain, meaning that the software is not accurate to validate the laboratory test.